Economic viability analysis of the implementation of a photovoltaic energy production in a small health business - Peroca, R.C; Amaral, M.C; Pacau, P.P; Vitali, P.M; Margotto, R.A.M (Journal of Innovation and Healthcare Management, 2019)
This article analyzed the tradeoff between cost and benefits related to the implementation of a photovoltaic system in a health business company, based on the electrical energy’s consumption. Beyond the financial return, this study estimated the CO2 emissions reduction. By the end of the study, is concluded that the discovery and progress of new technologies brings opportunities to transforming costs that were considered inevitable on evitable. It aroused the interest on making a new search find wastes, as well as the most common ones.